Financial well-being: financial ratio analysis of married public sector workers in Malaysia - Ramli, Zaimah; Masud, Jariah; Haron, Sharifah Azizah; Othman, Mumtazah; Awang, Abd Hair; Md Sum, Sarmila (Canadian Center of Science and Education, 2013)
The purpose of this study is to explore the usefulness of two family financial ratio guidelines in assessing the financial well-being of married public sector workers in Malaysia. The ratios examined were savings and debt-payment. Data on 415 workers were gathered from the Financial Well-being of Workers of Dual-earner Family survey report in 2008. The findings showed most of the workers had a savings ratio of less than 10 percent. Meanwhile, more than half of the workers had debt-payments ratio of more than or equal to 20 percent. In addition, the workers fall into four categories, namely are A, B, C and D, of which level A is the best and level D the worst. Typically, most of the workers are in level D (42.2%) and level B (30.1%). In summary, the study revealed that the culture of saving among the workers was still at the unsatisfactorily level.